The Prognostic Value of Bone Morphogenetic Proteins and Their Receptors in Lung Adenocarcinoma - Meng, Wangyang; Xiao, Han; Zhao, Rong; Li, Dong; Li, Kuo; Meng, Yunchong; Chen, Jiaping; Wang, Yangwei; Liao, Yongde (Frontiers in Oncology, 2021)
Background: Bone morphogenetic proteins (BMPs) regulate tumor progression via binding to their receptors (BMPRs). However, expression and clinical significance of BMPs/BMPRs in lung adenocarcinoma remain unclear due to a lack of systematic studies. Methods: This study screened differentially expressed BMPs/BMPRs (deBMPs/BMPRs) in a training dataset combining TCGA-LUAD and GTEx-LUNG and verified them in 4 GEO datasets. Their prognostic value was evaluated via univariate and multivariate Cox regression analysis. LASSO was performed to construct an initial risk model. Subsequently, after weighted gene co-expression network analysis (WGCNA), differential expression analysis and univariate Cox regression analysis, hub genes co-expressed with differentially expressed BMPs/BMPRs were filtered out to improve the risk model and explore potential mechanisms. The improved risk model was re-established via LASSO combining hub genes with differentially expressed BMPs/BMPRs as the core. In the testing cohort including 93 lung adenocarcinoma patients, immunohistochemistry (IHC) was performed to verify BMP5 protein expression and its association with prognosis. Results: BMP2, BMP5, BMP6, GDF10, and ACVRL1 were verified as down-regulated in lung adenocarcinoma. Survival analysis identified BMP5 as an independent protective prognostic factor. We also found that BMP5 was significantly correlated with EGFR expression and mutations, suggesting that BMP5 may play a role in targeted therapy. The initial risk model containing only BMP5 showed a significant correlation (HR: 1.71, 95% CI: 1.28- 2.28, p:3e-04) but low prognostic accuracy (AUC of 1-year survival: 0.6, 3-year survival: 0.6, 5-year survival: 0.63). Seventy-nine hub genes co-expressed with BMP5 were identified, and their functions were enriched in cell migration and tumor metastasis. The re-established risk model showed greater prognostic correlation (HR: 2.58, 95% CI:1.92- 3.46, p: 0) and value (AUC of 1-year survival: 0.72, 3-year survival: 0.69 and 5-year survival: 0.68). IHC results revealed that BMP5 protein was also down-regulated in lung adenocarcinoma and higher expression was markedly associated with better prognosis (HR: 0.44, 95% CI: 0.23- 0.85, p: 0.0145). Conclusion: BMP5 is a potential crucial target for lung adenocarcinoma treatment based on significant differential expression and superior prognostic value.